Level of Awareness on Selected Historical Sites in Metro Manila of Bachelor of Secondary Education Students at Bestlink College of the Philippines: Vol.3, No.1C (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This generation's establishments, buildings, and technology arise as time passes. The more our country develops, the less chance for the next generation to enjoy the historical sites, and soon enough will only be seen as pictures in books. The Historical sites in selected places in Metro Manila play an important role in preserving the things we have from the past. The EDSA Shrine, San Juan Bridge, Cry of Pugad Lawin, Kasa Boix in Quiapo, and Andres Bonifacio Shrine in Novaliches Plaza are some of the historical places that are barely identified as historical sites by most of the Bachelor of Secondary Education students at Bestlink College of the Philippines. Some of these places we are just passing through are the historical sites that have been part of our lives and history, hence this research. The researchers in this study attempt to determine the Level of Awareness on selected historical sites in Metro Manila using the descriptive-normative survey method. The primary subjects are the first-year, second-year, third-year, and fourth-year students enrolled in the Bachelor of Secondary Education major in Social Studies Students at Bestlink College of the Philippines for forty (40) respondents. To achieve population coverage, the sampling technique used in this research was stratified sampling. Additionally, Google Forms, a web-based questionnaire, was used to collect relevant data from the respondents. Furthermore, for the instrument validation, the adviser validated the questionnaire. It was distributed to 1-3 individuals not included in this research's total number of respondents to receive feedback before being distributed to the students. Finally, during the administration and retrieval of the questionnaire, the researchers communicated with the mayors of the social studies classes at each year level via messenger and Google Meet to discuss the questionnaire distribution.